PRESTASI BELAJAR MAHASISWA PADA METODE PEMBELAJARAN KELOMPOK TUTORIAL DI PRODI D III KEPERAWATAN - Nur Hasanah; Indriatie .; Made Sutarna (JURNAL PENELITIAN KESEHATAN, 2014)
Learning method is one factor that determines student learning outcomes. One of learning strategy that allegedly able to realize the situation of active and independent learning in students is a method of group tutorials. The purpose of this study was to analyze differences in student achievement between teaching methods and group tutorial learning methods lecture on subjects KDM.This research is a comparative analytical study, which uses cross-sectional design. Samples were students of second semester at Nursing Diploma III Study Program of  Soetomo Surabaya 2012/2013 amounted to 79 people, who were taken using simple random sampling. The data collection is conducted by the method of documentation studies using the checklist instrument.From the results of hypothesis testing by using paired "t" test obtained probability value of 0.074 which is greater than the significance level of 0.05. That is, there was no significant difference between the students achievement in teaching methods and group tutorial learning methods lecture. This is understandable given the group tutorial learning method is a new experience lived. Which in practice not considered optimal.  Keywords: Method of group tutorial learning, learning achievement.